Comparison of Effectiveness of Ropivacaine Infusion Regimens for Continuous Femoral Nerve Block for Recovery After Total Knee Arthroplasty: A Randomized Double-Blind Trial - Zhang, Yujian (J Pain Res, 2020)
PURPOSE: Continuous femoral nerve block (cFNB) is effective for analgesia after total knee arthroplasty (TKA). However, it is not clear which low-dose regimen of ropivacaine infusion for cFNB provides adequate analgesia and enables rapid recovery. The aim of this study was to compare the effects of different cFNB regimens on rehabilitation of patients after TKA. PATIENTS AND METHODS: Sixty patients scheduled for TKA were enrolled in this trial. After surgery, patients in the 0.1%, 0.15%, and 0.2% ﻿groups received infusion of 10 mL of 0.1%, 6.7 mL of 0.15%, and 5 mL of 0.2% ropivacaine per hour, respectively (n=20), at the dose of 10 mg/h for 48 h. The primary endpoint was time to readiness for discharge. The secondary endpoints were time to first walk, manual muscle testing (MMT) scores, numerical rating scale (NRS) scores at rest and movement, morphine consumption, rescue analgesia, and the incidence of adverse events. RESULTS: The time to readiness for discharge and the time to first walk of the 0.1% ﻿group were significantly longer than that of the 0.15% and 0.2% ﻿groups. MMT scores of the 0.2% ﻿group at 18 h after surgery were significantly lower than those of the 0.1% group. MMT scores of the 0.2% ﻿group at 24 and 48 h after surgery were also significantly lower than those of the 0.1% and 0.15% ﻿groups. NRS scores at rest and at movement in the 0.1% ﻿group were significantly higher than those in the 0.15% and 0.2% ﻿groups. CONCLUSION: Patients administered the regimens of 0.15% and 0.2% ropivacaine infusion for cFNB were ready for discharge earlier than the 0.1% ﻿group after TKA, at the dose of 10 mg/h for 48 h. The regimen of 0.15% ropivacaine, which is associated with less quadriceps muscle strength weakness than 0.2%, is recommended for postoperative analgesia after TKA.